Carboxylated β-cyclodextrin anchored hollow mesoporous silica enhances insecticidal activity and reduces the toxicity of indoxacarb. (15th August 2021) - Yang, Liupeng; Kaziem, Amir E.; Lin, Yigang; Li, Chao; Tan, Yuting; Huang, Suqing; Cheng, Dongmei; Xu, HanHong; Zhang, Zhixiang
Abstract: In this study, a pesticide controlled release system with dual response characteristics of pH and enzyme triggering was developed. Indoxacarb (IDC) was loaded into hollow mesoporous silica (HMS) nanoparticles, carboxylated β-cyclodextrin (β-CD) acted as a capping molecule to couple with the amino-functionalized HMS, and their well-defined morphological structures were confirmed by scanning electron microscopy and transmission electron microscopy. The results showed that the prepared IDC loaded HMS-CD had high loading efficiency (26.42%, w/w) and showed excellent dual response properties to pH and the α-amylase enzyme. IDC loaded HMS-CD nanoparticles showed better insecticidal activity against Spodoptera frugiperda than applying the same dose of IDC emulsifiable concentrate, and the toxicity of IDC loaded HMS-CD to zebrafish was reduced by more than 5-fold, indicating that insecticide delivery systems based on β-CD-anchored HMS nanoparticles could potentially be applied for sustainable control of pests and reduce harm to non-target organisms and the environment. Graphical abstract: Unlabelled Image Highlights: A stimuli-responsive carrier was fabricated employing β-CD as the gatekeeper of HMS. IDC loaded HMS-CD displayed excellent dual-responsive α-amylase and pH properties. The prepared IDC loaded HMS-CD had good UV radiation stability. The IDC loaded HMS-CD had a longer duration of excellent insecticidal activity. The IDC loaded HMS-CD was significantly less toxic to zebrafish than IDC EC.